Meningkatkan Pengenalan Huruf Hijaiyah Melalui Metode Iqra (Pengabdian Masyarakat di Desa Kertajaya Kecamatan Cigugur Kabupaten Pangandaran) - Tantowie, Tanto Aljauharie; Firdaus, Anisa (Khidmat, 2021)
Teaching children in the art of reading the Koran is a challenging endeavour. In addition to possessing knowledge, an educator must also be familiar with the methodologies employed in the process of learning. The objective of this paper is to assess the implementation of the iqra technique as a fundamental approach to reading the Al-Qur'an at the At-Taqwa Mosque, located in Cibungur Hamlet, Kertajaya Village. This paper employs qualitative research methodology. The data collecting methods include of interview guides, observation, and documentation. These methods are used to gather and analyse data on the use of the iqra' technique, which aims to develop fundamental reading skills of the Al-Qur'an at the At-Taqwa Mosque, located in Cibungur Hamlet, Kertajaya Village. The research findings indicate a notable improvement in the proficiency of reading the Al-Qur'an using the iqra' technique at the At-Taqwa Mosque, located in Cibungur Hamlet, Kertajaya Village. This demonstrates that a significant proportion of children derive pleasure from acquiring knowledge of the Al-Quran through the iqra' approach, thereby enabling them to achieve fluency in reading the Al-Qur'an and proficiency in recitation.